"Is Granny Going Back into the Computer?": Visits and the Familial Politics of Seeing and Being Seen in South African Transnational Families. (4th July 2021) - Marchetti-Mercer, Maria; Swartz, Leslie; Baldassar, Loretta
ABSTRACT: Migration is an increasingly common feature of life globally. This article discusses visits in South African transnational families of diverse origins, exploring the importance and meaning of physical co-presence by examining the role of visits in delivering mutual 'visibility' – the ability to see and be seen – when family members meet in person. The data come from a qualitative project exploring South African transnational family relationships, and particularly, differences between the experiences of those who migrate and of those left behind. 'Outward', 'return' and 'reunion' visits are considered. One element visits had in common was excitement linked to the planning of the visit and actual visit, but there was also some ambivalence and underlying sadness, because visits provide only a temporary experience of physical co-presence. The multiple meanings attached to visits have implications for how family and care relationships are understood in the contemporary globalised world. Future research should consider the complexities of relationships and care through the transnational family lifecycle.